OCT RNFL and Macular GCC - Nisha Chaudhary; Neha Sachdeva; Umesh Sharma (Delhi Journal of Ophthalmology)
Subjective errors in disc evaluation and visual field analysis is one of the major factor which reduces reliability of diagnosing and monitoring glaucoma progression. Optical coherence tomography (OCT) retinal nerve fibre layer and macular ganglion cell complex in glaucoma are non contact, rapid and reliable methods to detect both pre perimetric glaucoma and its progression.